A Recommendation Expressed by a Coordinate Sentence with a Conditional Interclausal Semantic Relation - Šafer, Marina J. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
This paper examines a type of coordinate sentence in which a conditional–consecutive semantic relation can be observed between the clauses: the first clause contains a recommendation, while the second functions as a promise that follows once the recommended action is carried out. Such a compound sentence can be transformed into a complex sentence with a conditional clause, since performing the recommended action represents the condition for the announced positive consequence—that is, the promise—to take effect (cf. Do this exercise ten minutes before going to bed and you will forget about insomnia → If you do this exercise ten minutes before going to bed, you will forget about insomnia). The corpus comprises online texts belonging to the journalistic functional style, sourced from various websites (such as b92.net, zena.blic.rs, direktno.rs, muskimagazin. rs, etc.). It specifically targets sections that offer lifestyle recommendations, including health, fashion, home décor, plant care, and similar topics. The analysis focuses on the syntactic properties of such compound sentences (the presence or omission of conjunctions, the verbal forms of predicates in both clauses, etc.), alongside their semantic properties (the lexical semantics of the verbs realizing the predicates) and pragmatic functions (the speech acts performed by the clauses). The corpus shows that such sentences are frequent in newspaper headlines, with predicates most commonly realized by the imperative in the first clause and the future tense in the second. Additionally, a high frequency of the verbs forget and have is observed within the second clause. Elliptical clauses are also prominent in newspaper headlines (e.g. Two ingredients and dandruff will disappear → If [you use] two ingredients, dandruff will disappear).